The Students’ Engagement Realization in Academic Writing Flipped Classroom - Enny Dwi Lestariningsih; Testiana Deni Wijayatiningsih; Dian Ratu Ayu Uswatun Khasanah (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
They were teaching academic writing to fulfill the students’ ability in writing action research through blended synchronous faces some problems in this endemic COVID 19. Most issues are found in creating a face-to-face environment, but the condition is studied from home. We applied synchronous and asynchronous learning to academic writing courses using android gamification media to overcome this problem. The objective analysis of this current research is to investigate the effectiveness of android gamification media on academic writing courses through synchronous and asynchronous learning. The participants were 25 students from the second semester. The results showed that the implementation of android gamification media is effective in teaching academic writing courses through synchronous and asynchronous learning. The students’ engagement had positive results when the students learned academic writing through synchronous and asynchronous learning. Thus, this study contributes to the successful implementation of android gamification media through synchronous and asynchronous learning in academic writing courses.